Water sources and mixing in riparian wetlands revealed by tracers and geospatial analysis. Issue 1 (28th January 2016) - Lessels, Jason S.; Tetzlaff, Doerthe; Birkel, Christian; Dick, Jonathan; Soulsby, Chris
Abstract: Mixing of waters within riparian zones has been identified as an important influence on runoff generation and water quality. Improved understanding of the controls on the spatial and temporal variability of water sources and how they mix in riparian zones is therefore of both fundamental and applied interest. In this study, we have combined topographic indices derived from a high‐resolution Digital Elevation Model (DEM) with repeated spatially high‐resolution synoptic sampling of multiple tracers to investigate such dynamics of source water mixing. We use geostatistics to estimate concentrations of three different tracers (deuterium, alkalinity, and dissolved organic carbon) across an extended riparian zone in a headwater catchment in NE Scotland, to identify spatial and temporal influences on mixing of source waters. The various biogeochemical tracers and stable isotopes helped constrain the sources of runoff and their temporal dynamics. Results show that spatial variability in all three tracers was evident in all sampling campaigns, but more pronounced in warmer dryer periods. The extent of mixing areas within the riparian area reflected strong hydroclimatic controls and showed large degrees of expansion and contraction that was not strongly related to topographic indices. The integrated approach of using multiple tracers, geospatial statistics, and topographic analysis allowed us to classify three main riparian source areas and mixing zones. This study underlines the importance of the riparian zones for mixing soil water and groundwater and introduces a novel approach how this mixing can be quantified and the effect on the downstream chemistry be assessed. Key Points: Estimate the extent and dynamics of source waters in a riparian area Use geospatial information to estimate the spatial extent of source waters Source waters are highly dynamic and strongly influence by climatic conditions